Detection and Characterization of Bovine Rumen Microorganisms Resistant to Sodium Fluoroacetate - Pimentel, Maria Fernanda Aranega; Jesus Paula, Daphine Ariadne; Riet-Correa, Franklin; Dutra, Valéria; Nakazato, Luciano (Acta Scientiae Veterinariae, 2019)
Background: Poisoning of animals due to toxic plants is found in Brazil and other countries. One of the known toxic plants in Brazil, with the active ingredient sodium fluoroacetate (SF), is Palicourea marcgravii. Dehalogenases that inactivate the fluor-carbon bonds are enzymes found in microorganisms and may prevent intoxication. This study evaluated the occurrence of rumen microorganisms naturally resistant to SF. Materials, Methods & Results: Two samples of rumen fluid of cattle from the Experimental Farm of Federal University of Mato Grosso fed with Brachiaria sp. were obtained via fistula in flasks. An aliquot of 2 mL was placed in a microtube and centrifuged at 9000 g for 1 min. Then, the sample was inoculated into 2 tubes, one containing 100 µL of clarified rumen fluid in 2 mL of modified liquid culture medium (0.1% ammonium sulfate, 0.1% potassium phosphate monobasic, 0.05% sodium phosphate dibasic, 0.01% magnesium sulfate, 0.01% yeast extract, pH 7.0) and 0.4% of SF and the other sample containing 2 mL of liquid culture medium and 100 µL of clarified rumen fluid. The 2 samples were incubated at 40°C for 24 h. Dilutions were performed under the same conditions every 24 h until the attainment of microorganisms resistant to SF, and the finaldilution containing 50 µL of each sample was plated in the middle containing SF (0.4%) and incubated at 40°C for 24 h for the isolation of bacteria. The bacterial colonies resistant to SF were identified by morphological methods, stained, and subjected to DNA extraction sequencing using the universal primers 27f and 1492r (16S rDNA) for the identification of the bacterial genus using Blast DNA identity analysis. These bacteria were cultured with and without SF (0.4%), and the presence of fluoride ions was detected by an ion-selective electrode (fluoride) during incubation for 0, 30, 60, 90, and 120 min. Two resistant microorganisms were isolated, one was a Gram-positive coccus and the other was a Gram-positive rod. DNA sequencing identified these organisms as Enterococcus faecalis (98% identity Genbank 1358689) and Bacillus sp. (89% identity Genbank 1358671). Fluoride ions were detected more at 60-min incubation time in both E. faecalis (0.0560 ppm) and Bacillus sp. (0.0488 ppm). Bioassay protection tests were performed in mice ofthe following four groups: negative control (NC) with saline administration, positive control (PC) with administration of plant containing SF, Bacillus group (BG) with administration of plant containing SF plus Bacillus sp., and coccus group (CG) with administration of SF and E. faecalis. Clinical signs were recorded, and statistical analyses were performed to confirm the differences in the groups. Bioassay protection tests showed clinical signs of intoxication in the PC group (83.3%), BG group (100%), and CG group (16.6%) but not in the NC group (0%), with a statistical difference between GC and PC groups (P < 0.05). Discussion: Several environmental bacteria possessing dehalogenase activity have been described, such as Pseudomonas sp., Moraxella sp., and Burkholderia sp. and Pigmentiphaga kullae and Ancylobacter dichloromethanicus isolated from the rumen. No previous study has yet reported an association between dehalogenase activity and E. faecalis, and the protection assay has been observed only in the E. faecalis group. Similar results were observed in experimental intoxication in goats that had previously consumed SF, with the microorganisms identified being Pigmentiphaga kullae and Ancylobacter dichloromethanicus. E. faecalis, isolated from the bovine rumen, exhibited a dehalogenase activity, which could help control animal poisoning by plants containing SF.